Streptococcus Alpha growth in gingivitis patientâs dental plaque after rinsing with green tea extract (Camellia Sinensis) - Kurniwati, Isti Endah; Handajani, Juni; Tandelilin, Regina TC. (Padjadjaran Journal of Dentistry, 2007)
Green tea (Camellia sinensis) has been widely known as a healthy drink since long time ago. One of the substances in green tea which can give health benefit is catechin, an antibacterial substance. The purpose of this research is to know the efficacy of rinsing with green tea extract to Streptococcus alpha growth on gingivitis patientâs dental plaque. The research subjects include 30 mild gingivitis patients, and these subjects are divided into two groups: treatment group (20 patients) and control group (10 patients). Ten patients of treatment group rinse their mouth with 0.25% green tea extract and 10 other patients with 0.5% green tea extract. Meanwhile, control group use Bactidol (0.1% Hexetidine). Rinsing the mouth is performed every morning and night for five days. Sampling is conducted on the first and sixth day. Before rinsing data is analyzed using ANOVA and the result shows a significant difference. ANAVA testing then is done using proportion value. ANAVA Testing result shows that there is no significant difference among the patients in the treatment group. This result indicates that the effect of rinsing with 0.25% and 0.5% green tea extract is equivalent to the control (0.1% Hexetidine) to inhibit S. alpha growth on mild gingivitis patientâs dental plaque. From these two concentrations, it has not been known which one is the most effective concentration to inhibit S. alpha growth on mild gingivitis patient.